Guidelines for overcoming hospital managerial challenges: a systematic literature review - Crema M; Verbano C (Dove Medical Press, 2013)
Maria Crema, Chiara Verbano Department of Management and Engineering, University of Padova, Vicenza, Italy Purpose: The need to respond to accreditation institutes' and patients' requirements and to align health care results with increased medical knowledge is focusing greater attention on quality in health care. Different tools and techniques have been adopted to measure and manage quality, but clinical errors are still too numerous, suggesting that traditional quality improvement systems are unable to deal appropriately with hospital challenges. The purpose of this paper is to grasp the current tools, practices, and guidelines adopted in health care to improve quality and patient safety and create a base for future research on this young subject. Methods: A systematic literature review was carried out. A search of academic databases, including papers that focus not only on lean management, but also on clinical errors and risk reduction, yielded 47 papers. The general characteristics of the selected papers were analyzed, and a content analysis was conducted. Results: A variety of managerial techniques, tools, and practices are being adopted in health care, and traditional methodologies have to be integrated with the latest ones in order to reduce errors and ensure high quality and patient safety. As it has been demonstrated, these tools are useful not only for achieving efficiency objectives, but also for providing higher quality and patient safety. Critical indications and guidelines for successful implementation of new health managerial methodologies are provided and synthesized in an operative scheme useful for extending and deepening knowledge of these issues with further studies. Conclusion: This research contributes to introducing a new theme in health care literature regarding the development of successful projects with both clinical risk management and health lean management objectives, and should address solutions for improving health care even in the current context of decreasing resources. Keywords: health lean management, patient safety, clinical errors, health care quality, clinical process improvement